Vývojové trendy a prevalence syfilis, gonorey, chlamydiální infekce a HIV/AIDS u osob s rizikovým sexuálním chováním;behaviorální, klinické a epidemiologické charakteristiky pacientů STD centra - Kuklová, Ivana; Kojanová, Martina; Běláček, Jaromír; Velčevský, Petr; Trýzna, Roman; Dražďáková, Marcela (Iga MZ ČR, 2012)
This research will be focused at the epidemiology of sexually transmitted diseases (syphilis, gonorrhoea, Chlamydia trachomatis and HIV/AIDS), especially in the context of sexual behavior of patients and their gender, age, education, condom use, commercial sexual activity and number of sexual partners. Formal statistical computations will be processed using the licence versions of SPSS and Statistica SW.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: infekce bakteriemi čeledi Chlamydiaceae; sexuálně přenosné nemoci; Socioeconomic Factors; Prevalence; HIV infekce; Unsafe Sex; HIV Infections; prevalence; dermatovenerologie; Sexually Transmitted Diseases; Sexual Behavior; gonorea; syfilis; socioekonomické faktory; Gonorrhea; Chlamydiaceae Infections; Syphilis; rizikový sex; sexuální chování